Pengembangan E-LKPD dengan Model Discovery-Inquiry Learning untuk Meningkatkan Kemampuan Representasi Matematis Siswa - Aulia, Kintan Wanda; Sutiarso, Sugeng; Rosidin, Undang (Mandalika Mathematics and Educations Journal, 2025)
This development research aims to produce a valid, practical, and effective E-Worksheet based on the discovery-inquiry learning model to enhance students’ mathematical representation ability. The urgency of this study is grounded in the low level of students’ mathematical representation ability and the limited availability of interactive learning media that can connect abstract concepts with real-world contexts. The use of a discovery-inquiry-based E-LKPD offers a potential solution by encouraging students’ active engagement in constructing understanding through exploration and concept discovery. The subjects of this research were seventh-grade students at SMP Negeri 4 Bandar Lampung during the 2024/2025 academic year. This study employed a Research and Development (R&D) method using the ADDIE development model. Data were collected through mathematical representation ability tests and analyzed using a t-test and N-Gain score. The developed E-LKPD was categorized as valid and practical. The effectiveness test showed that the E-LKPD significantly improved students’ mathematical representation ability, with an average N-Gain score of 0,561. Hypothesis testing t-test confirmed that the use of the discovery-inquiry-based E-LKPD is effective in enhancing students’ mathematical representation ability.